Phenotyping T-Core lines at Terbol station- Lebanon - Istanbuli, Tawffiq; Agrawal, Shiv Kumar; Hamwieh, Aladdin; Maalouf, Fouad (International Center for Agricultural Research in the Dry Areas, 2022)
Samples of 447 T-CORE lines and 15 repeated checks under the experiment code (M1F22_ca) were planted on December 30, 2021, at Terbol station field, Lebanon with 2 replications. Each line is planted in two rows with a total of 14 seeds. At f the flowering stage, increasing the number of lines affected by Fusarium wilt with a total of lines affected (9.5%) from both replications. The plants were harvested in June 2022 to continue taking the yield and yield component traits.